Effectiveness of a Self-Management Program for Patients with Type 2 Diabetes Mellitus - hongsawong, Sumalee (Journal of Health Science of Thailand, 2019)
This quasi-experimental study was carried out on two group with a pre and post-test design .Its aim was to study the effects of this self-management program of type2 diabetes mellitus patients. This study applied Bandura’s self-efficacy theory as a conceptual framework. The samples were 40 type 2 diabetes mellitus patients in outpatient department of Phonsai Hospital in Roi-Et Province. The patients were divided into two group. The first group or the experimental group was 20 patients receiving the self-management program, and the other 20 patients, the control group, received the standard care in diabetes clinic. The self-management program consisted of activites to be performed within 4 weeks. The first week was for mastery learning; the second week, learning experiences from successful patients (vicarious experience); the third week was for verbal persuasion; and the last weed was for self-appraisal. The study tools were developed from the Summary of Diabetes Self-Care Activities (SDSCA). Its reliability was examined by CVI = 0.85 and Cronbach’s alpha coefficient alpha = 0.82. Data were analyzed using the percentage, mean, standard deviation and Mann-Whitney U Test. An alpha level of 0.05 was set as statistically significant level. The results showed that after 4 weeks of participation, the mean scores of the five behaviors among the study participants were statistically significantly higher than those before the intervention. Comparing with the control, the experimental group had better self-management behaviors with regard to dietary intake, exercise, taking medicine, foot care and emotional relaxation. It is recommended that the self-management program should be integrated into the standard care in DM clinic in order to enhance self-efficacy among patients with type 2 diabetes.